2014
DOI: 10.1038/onc.2014.341
|View full text |Cite
|
Sign up to set email alerts
|

EBV-miR-BART7-3p promotes the EMT and metastasis of nasopharyngeal carcinoma cells by suppressing the tumor suppressor PTEN

Abstract: The epithelial-mesenchymal transition (EMT) is crucial to cancer progression and metastasis. Although multiple cellular miRNAs have been identified to regulate the EMT and metastasis in cancers, the role of viral miRNAs in cancer progression remains largely unknown. Nasopharyngeal carcinoma (NPC) is an Epstein-Barr virus (EBV)-associated malignancy typically characterized by its early metastasis. In the present study, we have discovered the involvement of a viral miRNA, EBV-miR-BART7-3p, in the EMT and metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
186
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(193 citation statements)
references
References 60 publications
7
186
0
Order By: Relevance
“…EBV-positive NPC cell line HONE1 was kindly provided by Professor George SW Tsao from the University of Hong Kong. 15 shPDCD4-SUNE1, shPDCD4-HONE1 and miR-374a and PDCD4 in nasopharyngeal carcinoma Y Zhen et al…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…EBV-positive NPC cell line HONE1 was kindly provided by Professor George SW Tsao from the University of Hong Kong. 15 shPDCD4-SUNE1, shPDCD4-HONE1 and miR-374a and PDCD4 in nasopharyngeal carcinoma Y Zhen et al…”
Section: Cell Culturementioning
confidence: 99%
“…Immunohistochemistry Immunohistochemistry of CCND1 (Santa Cruz Biotechnology, Santa Cruz, USA) was performed in NPC tissues according to a previous description. 6,[12][13][14][15]34 Stained tissue sections were evaluated separately by two pathologists blinded to the clinical parameters. For cytoplasmic staining, scoring was assessed based on the sum of cytoplasm staining intensity and the percentage of positive staining areas of cells.…”
Section: Collection Of Primary Npc and Non-cancerous Nasopharynx Specmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent experiments demonstrated that ebv-miR-BART4-5p regulates Bid expression in EBVaGC [65]. Cai et al [66] recently demonstrated in nasopharyngeal carcinoma that ebv-miR-BART7-3p, one of the most abundant viral miRNAs in EBVaGC, targets the tumor suppressor gene PTEN , and promotes epithelial-to-mesenchymal transition and tumor metastasis. …”
Section: Virus-driven Oncogenesismentioning
confidence: 99%
“…EBV and KSHV miRNAs deregulate the cell cycle [27,28,30 ,81], inhibit apoptosis [27,28,30 ,41,42 ,82-85] and promote cell migration and metastasis [86][87][88], all hallmarks of cancer. Based on the current knowledge, therapies targeting induced cellular oncomiRs and their viral orthologues are warranted to treat not only EBVinduced and KSHV-induced tumors but also non-viral lymphoproliferative diseases (Figure 1).…”
Section: Role Of Viral Mirnas In Herpesvirusassociated Cancersmentioning
confidence: 99%